Case Report: Neratinib Therapy Improves Glycemic Control in a Patient With Type 2 Diabetes and Breast Cancer - Angelis, Vasileios; Johnston, Stephen R. D.; Ardestani, Amin; Maedler, Kathrin (Frontiers in Endocrinology, 2022)
A critical decline of functional insulin-producing pancreatic β-cells is the central pathologic element of both type 1 and type 2 diabetes. Mammalian Sterile 20-like kinase 1 (MST1) is a key mediator of β-cell failure and the identification of neratinib as MST1 inhibitor with potent effects on β-cell survival represents a promising approach for causative diabetes therapy. Here we report a case of robust glycemia and HbA1c normalization in a patient with breast cancer-T2D comorbidity under neratinib, a potent triple kinase inhibitor of HER2/EGFR and MST1. The patient, aged 62 years, was enrolled in the plasmaMATCH clinical trial and received 240 mg neratinib once daily. Neratinib therapy correlated with great improvement in glucose and HbA1c both to physiological levels during the whole treatment period (average reduction of random glucose from 13.6 ± 0.4 to 6.3 ± 0.5 mmol/l and of HbA1c from 82.2 ± 3.9 to 45.6 ± 4.2 mmol/mol before and during neratinib). 18 months later, when neratinib was withdrawn, random glucose rapidly raised together with high blood glucose fluctuations, which reflected in elevated HbA1c levels. This clinical case reports the combination of HER2/EGFR/MST1-inhibition by neratinib for the pharmacological intervention to effectively restore normoglycemia in a patient with poorly controlled T2D and suggests neratinib as potent therapeutic regimen for the cancer-diabetes comorbidity.